EFISENSI DISTRIBUSI PENDAPATAN DALAM EKONOMI ISLAM - Abdul Qadir (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2021)
Transitions between production, distribution, and consumption in an economic system are inseparable from one another. If one of them experiences a problem, it will have an impact on all of them (economic problems occur scarcity), meaning that if one of the three foundations is scarce it will cause problems in the wheels of the economy. creates conflict, this is different from the economic system in Islam, that property should not be controlled by a handful of people or groups in order to have justice and distribution. The purpose of this paper is to find out how the distribution patterns of production in Islam and conventional. Meanwhile, the problem formulated is how the effectiveness of production distribution without having to harm one of the parties, so that the distribution will reach the market which is the meeting place between traders and consumers. The object of this study is focused on how the efficiency of distribution in Islamic and conventional economic systems, while the data used is in the form of scientific works and writings related to distribution, then the data analysis is a descriptive qualitative method. The theory used is related to distribution as Adiwarman A Karim's opinion, which states that justice in the distribution system does not have any parties being judged. The conclusion of the paper is that the efficiency of allocation and distribution of income based on the Islamic perspective can be said to be efficient if it has been fulfilled and there are no parties being judged.